COMPARISON BETWEEN THE POSTERIOR AND LATERAL APPROACHES OF THE POPLITEAL BLOCK FOR LOWER-LIMB EMERGENCY MINOR SURGICAL PROCEDURE: A PROSPECTIVE STUDY - SHAHENAZ N MASTER; DEEPA GONDALIYA; VANDNA S PARMAR; SANJU PRAJAPATI; HITARTHI DINESHBHAI VADSOLA; MONA JITUBHAI CHAVADA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to compare various factors such as technical difficulties, the onset of anesthesia, duration of anesthesia and analgesia, and the branches of the sciatic nerve stimulated for both the posterior and lateral approaches of the block. Methods: A study was conducted in a tertiary care hospital from March 2021 to September 2022. With the patients’ informed written consent, a total of 50 individuals undergoing lower-limb emergency minor surgical procedures were randomly assigned to two groups: Group L and Group P. Each group received a popliteal block (PB) using either a lateral or posterior approach. The patients were closely monitored to assess any technical difficulties associated with both approaches. Results: According to the study findings, the participants in Group L had a median age of 46, while those in Group P had a median age of 37. Our investigation revealed that patients in Group L required a notably higher number of attempts and a greater depth for induction (p=0.004; p<0.0001 respectively). However, there were no notable distinctions observed between the two approaches in terms of the time it took for pain relief to begin, the length of the surgical procedure, and the overall duration of pain relief (p=0.80; p=0.54 and p=0.36, respectively). Conclusion: The study found that patients who received lateral approaches for PB experienced more challenges during induction compared to those who received posterior approaches.